Improvement of Dynamic Buckling Behavior of Intermediate Aluminized Stainless Steel Columns - Al-Khazraji, Ahmed Naif; Al-Rabii, Samir Ali; Al-Khazaali, Hameed Shamkhi (Al-Khwarizmi Engineering Journal, 2017)
This paper experimentally investigated the dynamic buckling behavior of AISI 303 stainless steel aluminized and as received intermediate columns.  Twenty seven specimens without aluminizing (type 1) and 75 specimens with hot-dip aluminizing at different aluminizing conditions of dipping temperature and dipping time (type 2), were tested under dynamic compression loading (compression and torsion), dynamic bending loading (bending and torsion), and under dynamic combined loading (compression, bending, and torsion) by using a rotating buckling test machine. The experimental results werecompared with tangent modulus theory, reduced modulus theory, and Perry Robertson interaction formula. Reduced modulus was formulated to circular cross-section for the specimens of type (1).The experimental results obtained showed an advantageous influence of hot-dip aluminizing treatment on the dynamic buckling behavior of AISI 303 stainless steel intermediate columns. The improvements based on the average value of critical stress were19.4 % for intermediate columns type (2) compared with columns type (1) under dynamic compression loading, 8.7 % for intermediate columns type (2) compared with columns type (1) under dynamic bending loading, and 16.5 % for intermediate columns type (2) compared with columns type (1) under dynamic combined loading.